Multi-Dimensional Ayurvedic Management of Psoriasis Complicated With Arthritis – Acase Study - Bhoomi N. Prajapati; Dr. Meghana Chaudhari; Dr. Dharmishtha K. Garod (Asian Journal of Pharmaceutical Research and Development, 2026)
Background: Psoriatic arthritis (PsA), a heterogeneous chronic inflammatory immune-mediated disease characterized by musculoskeletal inflammation, generally occurs in patients with psoriasis.Conventional treatments such as non-steroidal anti-inflammatory drugs (NSAIDs), disease-modifying anti-rheumatic drugs (DMARDs), and biologic agents aim to alleviate symptoms and prevent joint damage. However, these treatments may have limitations such as side effects or inadequate control of symptoms in some patients. Psoriatic arthritis simulates Ayurvedic descriptions of the clinical syndrome - Vatarakta. The treatment principle focuses on controlling inflammation of affected joints to prevent joint pain and further disability. Brief case report: A 50-year-old female patient arrived to P D Patel Ayurveda hospital in Nadiad with a clinical diagnosis of Psoriatic arthritis. She was having blackish-red discolouration and itching all over body from last 3 years; pain and stiffness in all joints mainly in interphalangeal joints and various complaints from last 4 months. She wasunder modern medicaments but she could not get any satisfactory relief. So, the patient came for ayurvedic treatment which commenced with vardhamana pippali rasayanpra yoga and svedanakarma followed by virechankarma, pathyadibasti, raktamokshna karma and then after oral Ayurvedic medications viz., manjisthadikwatha, kaishoraguggulu, haridrakhanda, lelitakamakshik, simhnadaguggulu. Outcome: Itching, discoloration, pain, stiffness, insomnia, and other symptoms were reduced by 70–80% after five weeks of IPD treatment and six months of OPD treatment. The outcomes were positive. Conclusion: Positive result in the present case highlights the potential of multi-dimensionalayurveda treatment in managing Psoriatic arthritis (PsA) and will help to generate the hypothesis for further research.